The Future of the Transition to E-learning and Distance Learning Using Artificial Intelligence - El Gourari, Abdelali; Skouri, Mohammed; Raoufi, Mustapha; Ouatik, Fahd (2020 Sixth International Conference on e-Learning (econf), 2020)
Now, as you know, research in the world's recent times over the new Corona pandemic has revealed the need for education e-learning, distance learning, and what it is important to keep it moving. Support must be given to this vital and problematic area, which brought all educational institutions from the primary to the university to stop working suddenly and move from traditional to modern it is e-learning and distance learning in which they have used many skills. In this article, we will talk about The problem of how to move to e-learning and distance learning using modern techniques, and the very important thing that COVID-19 has revealed in the use and application of this type of education and the mechanisms to promote it within its educational systems. To properly develop and apply it, artificial intelligence technology, which in turn depends on the well-informed and rigorous analysis of student, teacher, scientific, and educational electronic environment, must be used.